2022
DOI: 10.1007/s10753-022-01661-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid as a Diagnostic Biomarker for Rheumatoid Arthritis–Associated Interstitial Lung Disease

Abstract: Previous studies have suggested a correlation between uric acid (UA) and lung lesion in some diseases. However, it remains unknown whether UA contributes to the lung injury in rheumatoid arthritis (RA). Our study aimed to investigate the clinical value of the UA level in the severity of rheumatoid arthritis–associated interstitial lung disease (RA-ILD). We measured UA in serum and bronchoalveolar lavage fluid (BALF), and UA levels of subjects were compared. As for the role of UA on ILD, we incubated A549 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In more detail, patients with higher SUA levels have a higher prevalence of pulmonary manifestations, namely interstitial lung disease (ILD) and a relationship between pSS-ILD and the occurrence of previous CV events has also emerged. In line with our findings, a recent study demonstrated that patients with ILD associated with RA display higher levels of SUA and also higher levels of bronchoalveolar lavage fluid (BALF)-UA [ 27 ]. A study using an experimental model of ILD demonstrated that bleomycin-induced lung injury triggers local production of UA, thereby activating the NALP3 inflammasome in the lung and perpetuating lung damage [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In more detail, patients with higher SUA levels have a higher prevalence of pulmonary manifestations, namely interstitial lung disease (ILD) and a relationship between pSS-ILD and the occurrence of previous CV events has also emerged. In line with our findings, a recent study demonstrated that patients with ILD associated with RA display higher levels of SUA and also higher levels of bronchoalveolar lavage fluid (BALF)-UA [ 27 ]. A study using an experimental model of ILD demonstrated that bleomycin-induced lung injury triggers local production of UA, thereby activating the NALP3 inflammasome in the lung and perpetuating lung damage [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study using an experimental model of ILD demonstrated that bleomycin-induced lung injury triggers local production of UA, thereby activating the NALP3 inflammasome in the lung and perpetuating lung damage [ 28 ]. In addition, higher SUA and BALF-UA levels have been associated with worse pulmonary function at spirometry not only in RA-ILD but also in healthy subjects [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among tests usually performed in the clinical setting, an unsuspected role has been proposed for serum uric acid, for which higher levels were observed in RA-ILD with a prevailing UIP pattern at HRCT ( 116 ). Serum uric acid is already included in the DETECT algorithm for early detection of pulmonary arterial hypertension in patients with systemic sclerosis (SSc) ( 117 ).…”
Section: Traditional and Novel Biomarkers In Ra-ildmentioning
confidence: 99%
“…A total amount of 1694 was excluded after the initial screening because of duplication or irrelevance to the search question. After reviewing the full text of the remaining 24 articles, a further five were removed because they failed to meet the inclusion criteria, leaving 19 studies, published between 1987 and 2022, for analysis (Tables 1 and S3) [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Legend: F, female; M, male; NR, not reported; *, µmol/L; • , mmol/L.…”
Section: Systematic Searchmentioning
confidence: 99%